Variables that influence academic performance and university persistence (European Journal of Education and Psychology, 2018)
University dropout has serious consequences not only for the student who gives up, but also for the host society itself. This has led to an increase in studies aimed at analysing and preventing dropout, implemented under different methodologies that are reported in this article.In addition to this trend, the authors – as members of the European Project ALFA GUIA – have developed a study using a holistic ex-post facto approach targeted at identifying those variables that play a fundamental role in university student? persistence. The sample used for the statistical analyses excluded students who had left one degree course to enrol on another (since there were no significant differences compared to the group that continued), and the cases with missing values. This resulted in a final sample of 677 subjects (198 who had dropped out and 479 who had persisted). A sample of 1300 university students was interviewed; the information was collected using a questionnaire collaboratively designed by the Project partners, and – in this case – by means of computer assisted interview. A descriptive and correlational analysis was carried out, as a first approximation to data, helping to identify the main relationships between variables. Based on these results, a binary logistic regression analysis was performed. The results confirmed that vocation is the variable that most influences persistence on the studies started. Therefore, this variable (vocation) can act as a protective factor against university dropout, once the remaining variables are controlled.